Multilingualism and Cultural Resistance in Bumi Manusia: A Critical Sociolinguistic and Postcolonial Analysis - Dewi Yulianti, Ni Ketut; P. Jesika Sita Devi N., I Gst. Ayu; Krisma Surya Deva N., I Gst. Bagus (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
This paper explores the complex relationship between language and culture in Bumi Manusia (This Earth of Mankind), a novel by Indonesian author Pramoedya Ananta Toer. Set during the Dutch colonial period in the early 20th century, the novel presents a multilingual environment where Dutch, Malay, and Javanese languages interact within a socially stratified society. The central research problem addressed is how language operates as both a tool of colonial control and a medium for cultural resistance and identity formation. Through the lens of critical sociolinguistics and postcolonial cultural theory, this study examines how linguistic practices in the novel reflect broader power dynamics, colonial ideologies, and cultural negotiations. The protagonist, Minke, embodies a linguistic and cultural hybrid, navigating between colonial education in Dutch and his native cultural roots expressed in Malay and Javanese. His linguistic choices mirror his shifting identity, revealing a deeper tension between imposed authority and indigenous self-determination. Pramoedya’s strategic use of multilingual narration is interpreted as a form of subversive storytelling that challenges the dominance of the colonial language while asserting the significance of native cultural perspectives. The novelty of this research lies in its interdisciplinary focus on how literature can function as a site of linguistic resistance and cultural recovery in the face of colonial hegemony. By analyzing the novel’s language politics, this paper contributes to broader discussions on the role of language in postcolonial identity formation and the intersection between linguistic power and cultural expression in Southeast Asian literature.